Gelatin production from turkey (Meleagris gallopavo) skin as a new source: from waste to a sustainable food gelling agent - Ozcan, Yilmaz; Kurt, Abdullah; Ozmen, Duygu; Toker, Omer Said (WILEY, 2023)
BACKGROUNDTurkey skin, a byproduct of poultry processing, contains a significant amount of collagen that might be used to make non-mammal gelatin. However, gelatin production from turkey skin has not yet been investigated. The present study aimed to determine the optimum gelatin extraction conditions from turkey employing the central composite design and response surface methodologies. The independent factors such as temperature (50, 60, and 70 degrees C) and time (5, 7, and 9 h) were optimized for three response variables: yield, gel strength, and foam expansion (FE). RESULTSWith R-2 values of 0.8576 for yield, 0.8386 for gel strength, and 0.9283 for foam expansion, linear, quadratic, and respective models were used. The yield, gel strength, and FE actual values were found to be 15.36%, 396.61 g, and 40%, respectively. The optimum extraction conditions were found to be 62.90 degrees C for 6.84 h. The foam stability, L, and b values were significantly impacted by temperature and extraction time (P < 0.05). CONCLUSIONThe gel strength value of the gelatin extracted under optimal conditions was higher than that of commercial bovine. The findings of the present study showed that turkey skin is a suitable raw material for the manufacturing of gelatin. (c) 2023 Society of Chemical Industry.
Keywords: turkey skin; gelatin extraction; optimization; functional properties; FUNCTIONAL-PROPERTIES; FISH GELATIN; GEL PROPERTIES; PHYSICOCHEMICAL PROPERTIES; EXTRACTION; TEMPERATURE; ACID; Agriculture; Chemistry; Food Science & Technology